Docência universitária nos cursos de artes UFU: formação, identidade e saberes - Bezerra, Paloma Oliveira (2015)
This study sets up a proposal developed in the field of research in Knowledge and Educational Practices, focusing mainly in the university teaching. Aiming to contribute with the debates about teaching at University, this study is an analysis of the university teaching learning process in the context of the Arts courses at UFU. The methodological option proposed was defined as qualitative, with an interpretative feature. The data construction was based on question and narrative interviews. The life history enabled the data analysi. Through the question, students of Visual Arts, Music and Theater pointed the professors that has contributed for their formation with their teaching process. After this step, we came to four teachers involved, who described their personal and professional path. Their narratives afford not just the database construction, but, especially, the creation itself, from the reflection. Question about the professors identity, formation, knowledge and teaching practice were made and questioned. Among the mainly results are the interlacing of the personal and professional in the construction/mobilization of knowledge in the academic daily; and personal identity development; the diversity of knowledge need/necessary for teaching; the link of teaching and artist practices in the academic daily; the teaching learning from the relation, in/from researches, in/from experiences; the university as a formation place; and the building of art knowledge; which the formation process occurred, in the course of life, in the extend which we give meaning to what happens to us. Thus, we came up with the expression of Teacherartist as evidencing an identity that is built at the confluence between art and education, although not without dilemmas. Thereby, we pointed the inextricable relationship among formation, identity, knowledge and practices through the narratives.